Savitri Goonesekere (ed.). Violence, Law and Women’s Rights in South Asia. New Delhi: Sage Publications, 2004. 352 pages. Paperback. Indian Rs 390.00. (The Pakistan Development Review, 2008)
The book titled Violence, Law and Women’s Rights in South Asia deals with a critically important issue for all countries, and particularly so for South Asian countries. In the latter, despite socio-cultural similarities, significant differences exist in handling gender-based violence. The issues are linked to the socio-cultural norms of the societies and the legal and institutional set-up prevailing in each country—viz., India, Pakistan, and Sri Lanka. The present study was initiated by United Nations Development Fund for Women (UNIFEM) in collaboration with United Nations Children’s Fund (UNICEF).